Binding properties of the anti-TB drugs bedaquiline and TBAJ-876 to a mycobacterial F-ATP synthase - Alexander Krah; Gerhard Grüber; Peter J. Bond (Current Research in Structural Biology, 2022)
Tuberculosis (TB), the deadly disease caused by Mycobacterium tuberculosis (Mtb), kills more people worldwide than any other bacterial infectious disease. There has been a recent resurgence of TB drug discovery activities, resulting in the identification of a number of novel enzyme inhibitors. Many of these inhibitors target the electron transport chain complexes and the F1FO-ATP synthase; these enzymes represent new target spaces for drug discovery, since the generation of ATP is essential for the bacterial pathogen's physiology, persistence, and pathogenicity. The anti-TB drug bedaquiline (BDQ) targets the Mtb F-ATP synthase and is used as salvage therapy against this disease. Medicinal chemistry efforts to improve the physio-chemical properties of BDQ resulted in the discovery of 3,5-dialkoxypyridine (DARQ) analogs to which TBAJ-876 belongs. TBAJ-876, a clinical development candidate, shows attractive in vitro and in vivo antitubercular activity. Both BDQ and TBAJ-876 inhibit the mycobacterial F1FO-ATP synthase by stopping rotation of the c-ring turbine within the FO domain, thereby preventing proton translocation and ATP synthesis to occur. While structural data for the BDQ bound state are available, no structural information about TBAJ-876 binding have been described. In this study, we show how TBAJ-876 binds to the FO domain of the M. smegmatis F1FO-ATP synthase. We further calculate the binding free energy of both drugs bound to their target and predict an increased affinity of TBAJ-876 for the FO domain. This approach will be useful in future efforts to design new and highly potent DARQ analogs targeting F-ATP synthases of Mtb, nontuberculosis mycobacteria (NTM) as well as the M. leprosis complex.